2023
DOI: 10.1038/s41467-023-36876-4
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish pigment cells develop directly from persistent highly multipotent progenitors

Abstract: Neural crest cells are highly multipotent stem cells, but it remains unclear how their fate restriction to specific fates occurs. The direct fate restriction model hypothesises that migrating cells maintain full multipotency, whilst progressive fate restriction envisages fully multipotent cells transitioning to partially-restricted intermediates before committing to individual fates. Using zebrafish pigment cell development as a model, we show applying NanoString hybridization single cell transcriptional profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 84 publications
(158 reference statements)
2
23
0
Order By: Relevance
“…Our results suggest a broader role for Ltk in specifying axolotl pigment cell fates, showing that Ltk knockdown affects iridophore, melanophore, and, presumably, xanthophore populations, as is observed in melanoid . A lesion that simultaneously affects the fate of multiple cell types supports the idea of a multipotent progenitor and direct fate specification ( Figure 7 C), as has been recently proposed for zebrafish pigment cell differentiation [ 10 , 16 ] and as was proposed in the single-origin hypothesis for pigment cells [ 8 ]. Additional studies are needed to determine if there are fundamental differences within amphibia in terms of how key genes function to regulate pigment cell fates.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our results suggest a broader role for Ltk in specifying axolotl pigment cell fates, showing that Ltk knockdown affects iridophore, melanophore, and, presumably, xanthophore populations, as is observed in melanoid . A lesion that simultaneously affects the fate of multiple cell types supports the idea of a multipotent progenitor and direct fate specification ( Figure 7 C), as has been recently proposed for zebrafish pigment cell differentiation [ 10 , 16 ] and as was proposed in the single-origin hypothesis for pigment cells [ 8 ]. Additional studies are needed to determine if there are fundamental differences within amphibia in terms of how key genes function to regulate pigment cell fates.…”
Section: Discussionsupporting
confidence: 79%
“…( B ) In zebrafish shady , Ltk knockout only affects the specification of iridophores and does not affect melanophore or xanthophore abundances, consistent with progressive fate specification of iridophores and xanthophores [ 31 ]. ( C ) A cyclical fate restriction model recently proposed for zebrafish [ 15 , 16 ] posits dynamic, direct fate specification from highly multipotent progenitor cells. Yellow circles denote xanthophore lineage cells, white circles denote iridophore lineage cells, and black circles denote melanophore lineage cells.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Neural crest cells were characterized by multiple pigment cell genes (Table 1) including ltk , which directs multipotent neural crest cell development into pigment cells in zebrafish [56], suggesting these cells are pigment cell progenitors. The detection of neural crest cells, red blood cells, and muscle cells predominately in trunk skin samples (Fig.1 e,f), is consistent with expectations of greater abundance of these cell types in the trunk skin than in the fins [30] given the potential to cut deeper into the dermal layer.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, these cells arose in response to specific ablation of melanocytes. Secondly, this subpopulation expresses markers that are associated with multipotent pigment progenitors cells found during development ( Brombin et al, 2022 ; Brunsdon et al, 2022 ; Budi et al, 2011 ; Johansson et al, 2020 ; Saunders et al, 2019 ; Subkhankulova et al, 2023 ). Thirdly, although this subpopulation expresses aox5 and some other markers associated with xanthophores, we showed that differentiated xanthophores are not ablated by the melanocyte-ablating drug neocuproine and this mitfa + aox5 hi subpopulation does not make new pigmented xanthophores following neocuproine treatment.…”
Section: Discussionmentioning
confidence: 99%